The Similarities and differences in idioms across languages and cultures (International conference on multidisciplinary science, 2025)
Idioms are fascinating linguistic phenomena that offer a unique window into the cultural nuances and historical developments of different societies. They are expressions whose meaning cannot be deduced from the literal meaning of their individual words, making them particularly challenging for language learners and intriguing for linguists. This article will explore the similarities and differences in idioms across various languages and cultures, shedding light on their universal and culture-specific aspects.